2016
DOI: 10.1007/978-3-319-46100-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Integrating and Inspecting Combined Behavioral Profiling and Social Network Models in Destiny

Abstract: In this paper two key venues of investigation in game analytics are combined: behavioral profiling and social network analysis. Both venues of research are well developed but combined they permit pattern evaluation across player performance and networks. Here, competitive networks covering almost 3.5 million players of the hybrid online shooter game Destiny are developed and combined with behavioral profiles based on match performance metrics and defined using archetypal analysis. The profiles are embedded in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Recently, authors have found application in social network analysis of online multi-player games to identify and investigate social communities, to identify cheaters, or recommend match partners [6,7,22,31,38,39] and to investigate the impact of social aspects on in-game behavior, game performance, engagement, and retention [33] in games and multi-user environments such as Ωorld of Ωar-craft, Second Life, or Destiny. Especially correlations between social network metrics and behavioral features or performance measures have been shown as valuable tools to utilize social network analysis [12,29,33].…”
Section: Social Network Analysis (Sna)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, authors have found application in social network analysis of online multi-player games to identify and investigate social communities, to identify cheaters, or recommend match partners [6,7,22,31,38,39] and to investigate the impact of social aspects on in-game behavior, game performance, engagement, and retention [33] in games and multi-user environments such as Ωorld of Ωar-craft, Second Life, or Destiny. Especially correlations between social network metrics and behavioral features or performance measures have been shown as valuable tools to utilize social network analysis [12,29,33].…”
Section: Social Network Analysis (Sna)mentioning
confidence: 99%
“…Especially correlations between social network metrics and behavioral features or performance measures have been shown as valuable tools to utilize social network analysis [12,29,33]. In [33], for example, the authors show correlations between strong social connections and collaborations, and in-game performance and engagement. Ωhile authors have shed light on social structures within online games through social network analysis, the use of this method to analyze the game development process is barely covered yet.…”
Section: Social Network Analysis (Sna)mentioning
confidence: 99%
“…Social relationships formed within and through online multiplayer games influence the engagement and user experience of players [1], [2]. Moreover, social relationships in games are essential drivers of retention and monetization in games [3], [4]. The facilitation and management of player communities and the connections between players is an important part of maintaining a healthy player base for a game and is vital for the survival of online multi-player games, which rely on a persistent presence [3], [4], [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, social relationships in games are essential drivers of retention and monetization in games [3], [4]. The facilitation and management of player communities and the connections between players is an important part of maintaining a healthy player base for a game and is vital for the survival of online multi-player games, which rely on a persistent presence [3], [4], [5], [6]. Building an understanding of how social connections are formed across such platforms -whether they are provided as part of a game or game distribution network or have grown around a game -and how connections can foster engagement, retention, or promote particular behaviors (e.g., to reduce toxicity among community members [7]), can thus offer actionable insights for companies to achieve this goal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation